2016
DOI: 10.1038/srep29296
|View full text |Cite
|
Sign up to set email alerts
|

No attentional capture from invisible flicker

Abstract: We tested whether fast flicker can capture attention using eight flicker frequencies from 20–96 Hz, including several too high to be perceived (>50 Hz). Using a 480 Hz visual display rate, we presented smoothly sampled sinusoidal temporal modulations at: 20, 30, 40, 48, 60, 69, 80, and 96 Hz. We first established flicker detection rates for each frequency. Performance was at or near ceiling until 48 Hz and dropped sharply to chance level at 60 Hz and above. We then presented the same flickering stimuli as pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…The similarity between attractive serial dependence and repulsive adaptation effects in vision is suggested by the observations that both phenomena emerge not only across "primary" visual dimensions such as orientation He & MacLeod, 2001), numerosity (Fornaciai & Park, 2018b;Arrighi, Togoli, & Burr, 2014), position (Manassi et al, 2018;Whitaker, McGraw, & Levi, 1997), motion (Alais et al, 2017;Kohn & Movshon, 2003), or shape (Manassi Kristjánsson, & Whitney, 2019;Mattar, Olkkonen, Epstein, & Aguirre, 2018), but also across more complex features such as the summary statistics of a visual scene (Manassi, Liberman, Chaney, & Whitney, 2017;Corbett, Wurnitsch, Schwartz, & Whitney, 2012) and visual variance (Suárez-Pinilla et al, 2018;Maule & Franklin, 2020). Moreover, although adaptation and serial dependence may involve distinct physiological mechanisms, there is evidence that the same stimulus can induce either an attractive or a repulsive effect, depending on whether it was actively judged (Pascucci et al, 2019), or whether it was visible or suppressed by backward masking (Fornaciai & Park, 2019a;.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The similarity between attractive serial dependence and repulsive adaptation effects in vision is suggested by the observations that both phenomena emerge not only across "primary" visual dimensions such as orientation He & MacLeod, 2001), numerosity (Fornaciai & Park, 2018b;Arrighi, Togoli, & Burr, 2014), position (Manassi et al, 2018;Whitaker, McGraw, & Levi, 1997), motion (Alais et al, 2017;Kohn & Movshon, 2003), or shape (Manassi Kristjánsson, & Whitney, 2019;Mattar, Olkkonen, Epstein, & Aguirre, 2018), but also across more complex features such as the summary statistics of a visual scene (Manassi, Liberman, Chaney, & Whitney, 2017;Corbett, Wurnitsch, Schwartz, & Whitney, 2012) and visual variance (Suárez-Pinilla et al, 2018;Maule & Franklin, 2020). Moreover, although adaptation and serial dependence may involve distinct physiological mechanisms, there is evidence that the same stimulus can induce either an attractive or a repulsive effect, depending on whether it was actively judged (Pascucci et al, 2019), or whether it was visible or suppressed by backward masking (Fornaciai & Park, 2019a;.…”
Section: Introductionmentioning
confidence: 95%
“…Specifically, it is an attractive bias in which the current stimulus appears mistakenly more similar to a previous one than it is in reality-much like an averaging of the features of successive stimuli. Serial dependence has been shown to be pervasive in vision, emerging in several visual domains spanning from relatively simple visual attributes such as orientation Fritsche, Mostert, & de Lange, 2017;Pascucci, Mancuso, Santandrea, Della Libera, Plomp, & Chelazzi" 2019), position (Manassi, Liberman, Kosovicheva, Zhang, & Whitney, 2018), numerosity (Corbett, Fischer, & Whitney, 2011;Fornaciai & Park, 2018a;Fornaciai & Park, 2018b) and motion (Alais, Leung, & Van der Burg, 2017) to more complex features such as face identity (Liberman, Fischer, & Whitney, 2014), attractiveness (Xia, Leib, & Whitney, 2016), and visual variance (Suárez-Pinilla, Seth, & Roseboom, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…secondary visual cortices). In agreement with these arguments, it has been repeatedly reported that invisible visual flickering is still able to activate V1 even without any perceptual effects (23), as revealed by in vivo electrophysiology in non-human primates (16) as well as behavioral evidence (24) and BOLD fMRI (25) in humans. High (30 Hz) frequency visual stimulation has been found to selectively suppress multi-unit activity (MUA) in cat V1 as compared to low frequency (4 Hz) visual stimulation (26).…”
Section: Introductionmentioning
confidence: 56%
“…secondary visual cortices). In agreement with 70 these arguments, it has been repeatedly reported that invisible visual flickering is still able to 71 activate V1 even without any perceptual effects (23), as revealed by in vivo electrophysiology in 72 non-human primates (16) as well as behavioral evidence (24) and BOLD fMRI (25) in humans.…”
Section: Introductionmentioning
confidence: 68%
“…The stimulus was back-projected onto the screen using a DLP LED projector (PROPixx, VPixx Technologies Inc., Montreal, Canada). The PROPixx operated in a specialized high refresh rate video sequencer mode called QUAD4X developed by VPixx Technologies (Alais et al, 2016;Balsdon et al, 2018;DeSimone & Schneider, 2019;Schweitzer & Rolfs, 2019;Zhang et al, 2019;Zhigalov et al, 2019). In short, the computer's graphic card (Titan V, Nvidia, Santa Clara, CA) transmits a 1920 x 1080 pixels image at 120 FPS.…”
Section: Design and Apparatusmentioning
confidence: 99%